Cyclic testing of unreinforced masonry walls in two-way bending. - Griffith, M. C. (Earthquake engineering & structural dynamics.)
An experimental programme was conducted in which eight full-scale unreinforced masonry walls were subjected to cyclic face loading using a system of airbags. Of the eight walls, six contained a window opening and four were subjected to vertical pre-compression. Combined supports at the vertical and horizontal edges ensured that under face loading the walls underwent two-way bending. The test walls were found to possess good post-peak strength and displacement capacity as well as reasonable energy dissipation characteristics. Significant strength and stiffness degradation and non-symmetry of strength in the positive and negative displacement directions were also evident. Discussion of the causes of the aforementioned trends and their implications towards the seismic response of masonry walls is provided.